NATIONAL FEATURES WHICH ARE NECESSARY TO BE DEVELOPED IN A PERSON - Taskarevna, Nishanova Zamira; Yuldibaevna, Baykunusova Gulmira; Batirovna, Atabaeva Nargis; Ziyodullayevna, Jorakulova Dildora (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses national consciousness, national traditions, ethnicity, and national characteristics that need to be developed in person. Numerous factors related to the nation and nation have played an important role in the social and political life and will continue to be relevant for a long time. According to scholars, there are about four thousand nations, ethnic groups and peoples who are at various stages of socio- economic and cultural development. Each of them has its own history, culture and national values. Studying them helps greatly in establishing inter-ethnic relations, establishing diverse economic and cultural ties. However, until recently, our social science system has underestimated the role of national issues and the psychological factors in it. In some cases, it was unreasonably denied. Some researchers have even questioned the study of national peculiarities, ethnopsychology. At the same time, they were concerned that the study of ethnopsychology would bring praise to one nation and discriminate against the other, causing racism and nationalism. There was a well- known reason for this fear. Some studies on ethnopsychology have led the authors to exaggerate their ethnicity and to outrage other neighboring nations, which naturally triggered various protests. At the same time, it is impossible to ignore the peculiarities of peoples in their perception of reality and nature, dress, upbringing, and intergenerational relationships. Denial of ethnic identity and ignorance in national relations can lead to various negative attitudes and even ethnic conflicts.